An effective and user-friendly web application for the collaborative analysis of steel joints. (May 2018) - Gracia, J.; Bayo, E.
Highlights: An effective 3D graphic web application for collaborative analysis of steel joints. Simple and fully rigid beam to column steel joints are considered. The latest cutting edge technologies are used to address visualisation and analysis. JavaScript frameworks and 3D WebGL API are used for the graphic interface. Rigorous and precise analyses of steel joints are performed according to Eurocode 3. Abstract: The Internet has increased its potential exponentially since its inception. This progress has been possible due to new standards and technologies, which have also allowed the development of a new type of web applications that are fully integrated in web browsers. In addition, structural analysis has become a collaborative task in which different people have to share information and outputs of analysis programs. In this paper, an effective and user-friendly web application for the collaborative analysis of steel joints is presented. The latest cutting edge technologies in the Internet are used to address fundamental issues inherent in structural analysis software such as visualisation, interaction, and structural evaluation. Specifically, WebGL API, part of the HTML5 standard, is used to solve the visualisation issues of the proposed application. A rigorous analysis of simple and rigid structural joints is performed according to the standards and criteria set by the Eurocode 3.